History in the primary school (Historia, 2021)
Before one can start talking on history and the teaching of history, one must establish exactly what is meant by history. The word is derived from the original Greek word "Historia", which means literaly "knowledge acquired through investigation". It embraces the thing investigated -that is the object or (the past) and the investigator -the subject. The investigator or Historian narrates the thing investigated which is the past. The point to remember is that there is always a lapse of time between the incident and the narrative. An eye witness may write down his account of an event immediately after it has taken place or an historian may investigate and record it a hundred years later. This narrative is not the incident nor the past, it is an account by a witness or the investigator of what happened. No one can revive the incident or cause it to be re-enacted in order that he may observe and describe it. What has been, belongs to the unremitting past.
Keywords: History; History teaching; Curriculum; Primary schools; History as subject